PENERAPAN PENDEKATAN SUPERVISI KOLABORATIF DALAM MENINGKATKAN KEMAMPUAN GURU MENYUSUN SOAL TES SEMESTER - Wuryani, Ninik (Jurnal Inovasi Pembelajaran di Sekolah, 2022)
The act of making questions as an assessment instrument cannot be carried out arbitrarily, to improve the quality of teachers in making questions, it is necessary to know about making tests. However, it was found that there were many written test questions for the semester that the teachers of SDN Gisikdrono 03 Semarang City did not comply with the rules of writing questions. Of the 18 teachers there are only 5 teachers or 28% of teachers who are able to make written test questions according to the rules. Written test items that are not correct from the point of view of the rules of writing questions must be immediately corrected or replaced with new items. This of course requires the role of the principal by carrying out academic supervision activities that can be carried out with group techniques through collaborative supervision methods for teachers. This study is intended to answer the problem of whether the implementation of supervision with a collaborative approach can improve the ability of teachers in preparing semester test questions at SDN Gisikdrono 03 Semarang City for the 2021/2022 academic year? These problems are discussed through school action research which is carried out through 2 cycles with each cycle the stages are planning, action, observation and reflection. The results show that supervision with a collaborative approach can improve the ability of teachers in preparing semester test questions at SDN Gisikdrono 03 Semarang City for the 2021/2022 academic year. Then the implementation of supervision with a collaborative approach can improve the ability of teachers in preparing semester test questions at SDN Gisikdrono 03 Semarang City in the 2021/2022 academic year, this can be seen from the increase in the results of teacher professionalism in classroom administration management per cycle where in the first cycle there are 12 teachers or 66% and in the second cycle there were 17 teachers or 94%. These results indicate that these results are in line with expectations. An increase also occurred in teacher activities in participating in mini workshops where in the first cycle there were 11 teachers or 61% and in the second cycle there were 16 teachers or 89%. The increase in the implementation of collaborative supervision is an effective way for school principals to improve the ability of teachers to develop learning tools.